A Summation Formula for Estimating the Surface Areas of Ellipsoids (Journal of Computational Mathematics, 2004)
In this paper a summation formula for finding the surface area of general ellipsoids is derived.
Keywords: Ellipsoid; Prolate spheroid; Oblate spheroid; Summation formula.